Immune thrombocytopenia. Issue 11 (2nd November 2021) - Bussel, James; Cooper, Nichola; Boccia, Ralph; Zaja, Francesco; Newland, Adrian
ABSTRACT: Introduction: Primary immune thrombocytopenia (ITP) is an autoimmune disorder characterized by a low platelet count (<100 × 10 9 /L) with an increased risk of bleeding. Recent (2019) guidelines from the International Consensus Report (ICR) expert panel and the American Society of Hematology (ASH) provide updated recommendations for the diagnosis and management of ITP. Areas covered: The 2019 ICR and ASH guidelines are reviewed, and differences and similarities highlighted. Clinical approaches to the treatment of ITP are discussed, including the role of fostamatinib which is an approved treatment option in adult patients who are refractory to other treatments. Expert opinion: The 2019 ICR and ASH guidelines reflect recent changes in the management of ITP. Current treatment approaches for ITP are more rational and evidence-based than in the past. Patients should be treated based on their needs rather than on disease stage, and patient-specific outcomes, (e.g. quality of life) should be considered. Whilst corticosteroids are the mainstay of initial ITP treatment their use should be limited. For subsequent treatment, the use of thrombopoietin receptor agonist (TPO-RA) agents, fostamatinib and rituximab in adults is supported by robust evidence. Rituximab and recently approved fostamatinib offer viable alternatives to splenectomy.